Produtividade na indústria brasileira entre 1990 e 2002: comparação entre indústrias de processo e de montagem - Andrade, Márcio Rodrigues de (2011)
The purpose of this research is to determine and analyze the differences in the behavior of labor productivity between the process industry and assembly industry in the period 1990 to 2002. The main hypothesis which led to implementation of the study was that labor productivity growth in the assembly industry would have been higher than the labor productivity growth in the process industry. The reason for this lay in evidence in the literature showing that the adjustment of firms to new competitive context of the Brazilian economy was, mainly in their initial stages, through the adoption of modern management techniques and tools that were based on the toyota production system or lean production. Also according to this type of literature, such techniques and tools were most appropriate, and therefore more widespread, in the assembly industry. To achieve the objective and confirm or refute the hypothesis, the work was divided into four chapters. The first deals with the process of globalization and related issues, such as changes in industrial structure and economic reforms. The second chapter is devoted to discussing the concept of productivity and the results of several studies on the behavior of productivity in the Brazilian economy. The third chapter presents the characteristics of the process industry and industrial assembly.. The fourth chapter presents the methodology used to calculate the labor productivity in these different industries and presents also the results of calculations of labor productivity for the process industry and assembly industry made from three databases made available by IBGE. The main conclusion was that, especially in the period 1990 to 1996, growth in labor productivity in the assembly industry was actually higher than the growth of productivity in the process industry.